Jangin In Oral Gayo Literature: A Fusion Of Entertainment, Tradition, and Environmental Wisdom - Rismawati Rismawati; Jusnaini Hasni; Giovanni Oktavinanda; Nurrahmah Nurrahmah (Getsempena English Education Journal, 2026)
Jangin is a type of oral poetry performed in the Gayo language with distinct rhythms. It contains expressions of feelings, guidance, satire, and social and spiritual observations. This paper attempts to analyze the form, function and cultural values of jangin as intangible cultural heritage. This research is an ecological approach by using hermeneutic theory and content analysis to understand the meaning of the jangin text. The results showed that jangin consists of poetic stanzas, recited in Gayo language with characteristic rhythms, and has themes of religiosity, romanticism, social critique, and ecological awareness. Functionally, jangin was not only used for entertainment but also as a medium for moral education, social communication, and environmental wisdom preservation. The cultural values embedded in the practice of jangin reflect the strong ties of the Gayo community to nature, spirituality, and collective identity. The study highlighted the importance of preserving jangin as an intangible cultural heritage in relation to global cultural and environmental issues.